2008
DOI: 10.1099/mic.0.2007/013805-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline alters drug susceptibility in Candida albicans and other pathogenic fungi

Abstract: The tetracycline (TET) promoter has been used in several systems as an inducible regulator of gene expression. In control analyses, the standard Candida albicans laboratory strain SC5314 was found to have altered susceptibility to a variety of antifungal drugs in the presence of relatively high concentrations (50-200 mg ml "1 ) of TET. Altered susceptibility was most notable with exposure to amphotericin B (AMB), with a 32-fold increase in susceptibility, and terbinafine (TRB), with a 32-fold decrease in susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 43 publications
2
60
0
2
Order By: Relevance
“…Mitochondrial mutants of C. glabrata are more sensitive to amphotericin B (9, 86). Decreased susceptibility to this drug was also observed for C. albicans treated with tetracycline; this was attributed to the effects of tetracycline on the function of mitochondria (66). Tetracycline also increased the sensitivity to amphotericin B of C. neoformans and Aspergillus fumigatus (66), implying that mitochondrial roles in polyene tolerance are broadly conserved in pathogenic fungi.…”
Section: Mitochondria and Plasma Membrane-targeting Drugsmentioning
confidence: 78%
See 1 more Smart Citation
“…Mitochondrial mutants of C. glabrata are more sensitive to amphotericin B (9, 86). Decreased susceptibility to this drug was also observed for C. albicans treated with tetracycline; this was attributed to the effects of tetracycline on the function of mitochondria (66). Tetracycline also increased the sensitivity to amphotericin B of C. neoformans and Aspergillus fumigatus (66), implying that mitochondrial roles in polyene tolerance are broadly conserved in pathogenic fungi.…”
Section: Mitochondria and Plasma Membrane-targeting Drugsmentioning
confidence: 78%
“…Decreased susceptibility to this drug was also observed for C. albicans treated with tetracycline; this was attributed to the effects of tetracycline on the function of mitochondria (66). Tetracycline also increased the sensitivity to amphotericin B of C. neoformans and Aspergillus fumigatus (66), implying that mitochondrial roles in polyene tolerance are broadly conserved in pathogenic fungi. Moreover, a large study by Hillenmeyer et al that included 1,144 chemical genomic assays in S. cerevisiae found a significant enrichment in the GO (Gene Ontology) terms "mitochondrial inheritance," "mitochondrial localization," and "mitochondrial distribution" among genes required for wild-type fitness in the presence of nystatin (38).…”
Section: Mitochondria and Plasma Membrane-targeting Drugsmentioning
confidence: 78%
“…Mitochondrial membrane potential was evaluated using the fluorescent probes rhodamine 123 and MitoTracker green (Invitrogen) (60,61), according to the manufacturer's recommendations. Yeasts were grown in Sabouraud liquid medium as described above and suspended at 10 7 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…FLC indirectly inhibits ergosterol synthesis by the inhibition of microsomal cytochrome P450, whereas AMB interacts directly with ergosterol in the plasma membrane. Additionally, recent publications (37)(38)(39)(40)(41)(42) have suggested that the antifungal activity of AMB might also be mediated by oxidative damage. …”
Section: Discussionmentioning
confidence: 99%